DETERMINING THE SCALE OF A TOPOGRAPHIC MAP: DETERMINING THE SCALE OF A TOPOGRAPHIC MAP - Ivanov, Sabin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article shows all methods for determining the scale of a topographic map. the methods shown can be used when the scale is not displayed on the map.